MODERATING ROLE OF ORGANIZATIONAL COMMITMENT IN THE INFLUENCE OF WORKLOAD AND JOB BOREDOM ON CYBERLOAFING - Ni Made Devi Devanthi; Handoyo, Sarwo Edy; Arifin, Andi Harmoko (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2025)
In this digital era, cyberloafing—using the internet for personal purposes amid working hours—is progressively prevalent within the working environment, including within government institutions. Civil servants, as the backbone of public service, are expected to preserve work efficiency; however, widespread internet access opens opportunities to abuse working hours for personal online activities. This study intends to explore the influence of workload and job boredom on cyberloafing behaviour and the moderating role of organizational commitment among civil servants in Central Jakarta. The research employed a quantitative method with data collected through surveys. The data was analysed using Structural Equation Modelling (SEM) with AMOS 30. The results indicate that both workload and job boredom have a positive and significant effect on cyberloafing behaviour. Conversely, organizational commitment affects cyberloafing negatively and significantly. Furthermore, organizational commitment was found to weaken the positive influence of these variables. These findings highlight the importance of reinforcing organizational commitment to minimize cyberloafing behaviour among civil servants.